ANALISIS E-COMMERCE BERBASIS MARKETPLACE YANG BERPERAN MEMBANTU WIRAUSAHA PEMULA DALAM MENJALANKAN BISNIS - Thomas Sumarsan Goh; Erika Erika; Henry Henry; Albert Albert; Edison Sagala (Indonesian Journal of Economics, Entrepreneurship, and Innovation, 2021)
Entrepreneurship is needed to open job vacancies. This study focuses on entrepreneurs who start a business with e-commerce with the interview method. With marketplace-based e-commerce, all the products displayed in it will be easier for people to see. In using the marketplace, the responsibility of business actors must also be applied. The results of this study indicate that entrepreneurs who are new to running a business are mostly assisted by marketplace-based e-commerce to market their new products and consumers will easily find the products they need efficiently and without having to spend a lot of time. to buy it. Entrepreneurs who use the marketplace must be able to maintain the products and quality offered to consumers so that these products can be trusted by everyone who visits online. In developing a business, convenience is the main thing in doing business, which can also make buyers feel more satisfied so that buyers will make a repurchase.